2008
DOI: 10.1007/s00247-007-0728-2
|View full text |Cite
|
Sign up to set email alerts
|

CT versus plain radiographs for evaluation of c-spine injury in young children: do benefits outweigh risks?

Abstract: C-spine CT is associated with a significant exposure to ionizing radiation and increases excess relative risk for thyroid cancer in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 25 publications
1
32
0
2
Order By: Relevance
“…Nearly one-third to one-half of all children with cervical cord injuries demonstrate neurologic deficits (15,16). Furthermore, 40% of spinal cord injuries are associated with head trauma, necessitating a complete cranial examination.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly one-third to one-half of all children with cervical cord injuries demonstrate neurologic deficits (15,16). Furthermore, 40% of spinal cord injuries are associated with head trauma, necessitating a complete cranial examination.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In children, the benefits of CT are less clear. CT scanning exposes children to approximately 10 -90 times more radiation than plain films (15). Children are more radiosensitive than adults, with the thyroid being particularly radiosensitive; there is a linear association between radiation dose and the incidence of thyroid cancer.…”
Section: Computed Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Cerca del 32% de los pacientes con lesiones neurológicas asociadas a la fractura de columna no son diagnosticados al momento del daño, principalmente en pacientes que presentan disminución del nivel de consciencia por traumatismo craneal y en pacientes con daños asociados en la pelvis y en las extremidades 7,8 . La tomografía computarizada ha reemplazado a las radiografías convencionales como la imagen de elección primaria en los pacientes traumatizados, debido a su alta agudeza diagnóstica y a su costo-beneficio, reduciendo el número excesivo de radiografías tomadas [9][10][11] . La columna vertebral en los niños tiene más tejido blando y más periostio comparados con los adultos, resultando en un mayor potencial para la reparación de sus lesiones, la remodelación ósea, la cicatrización de los ligamentos dañados y la recuperación del daño neurológico [12][13][14] .…”
Section: Introductionunclassified
“…16 The risk was found to increase threefold for both malignancies, which due to their relative rarity would result in one extra case of each per 10,000 head CT examinations. For cervical spine imaging, Jimenez et al 17 demonstrated that the IR dose to the thyroid, where there is a linear association between IR dose and the development of cancer, was 90e200 times that of the conventional two or three plain film radiographs. This translated to twice the excess risk of developing thyroid cancer for children aged up to 4 years old.…”
Section: Introductionmentioning
confidence: 99%